Relationship Between Peer Popularity and Self-Esteem Among Young Pregnant Out of Wedlock - Nor Jumawaton Shahruddin; Mariani Mansor; Zainal Madon; Hanina Halimatusaadiah Hamsan (Asian Social Work Journal, 2017)
This study examined the relationship between peers popularity and self-esteem within the attitude towards sexual behaviour among young pregnant out of wedlock. A total of 130 teenagers pregnant out of wedlock aged between 14 years and 19 years from 4 welfare institutions in the states of Selangor, Perak, Johor and Kelantan participated in this research. Respondents were selected using stratified random sampling technique. This study utilises the three questionnaires of the Inventory Peer Pressure, Popularity, and Conformity Scale (Santor, Messervey & Kusumakar, 2000), the Rosenberg Self- Esteem Scale (Rosenberg, 1965) and Brief Sexual Attitudes Scale (Hendrick & Reich, 2006). All instruments used had yielded a Cronbach’s alpha reliability coefficient value ranging from 0.82 to 0.90. Findings revealed that the level of peers popularity is high, level of self esteem also high and respondents indicated a high level of attitude sexual behavior. Results of Pearson’s correlation analysis revealed that there were significant relationships between peers popularity and attitudes toward sexual behavior (r= .801, p<.05) and a significant correlation between self esteem and attitude sexual behavior (r = .708, p <.05). Bootstrapping analysis revealed the role of self esteem as a mediator variables of peers popularity and self esteem with sexual attitude behavior. From the theoretical implications, this study describes the role of self esteem as a mechanism that effect the popularity of peer sexual behavior and attitude. In conclusion, peers popularity and self esteem related to sexual attitude and behavior. The study showed that risk factors such as the acceptance by the peer group have a significant direct effect on sexual behavior At the same time, this study also suggests several alternatives in order to curb sexual misconduct among the teenagers today.